Tracing the origin of Traditional Chinese Medicine exercise therapy (中医运动疗法溯源) - ZHOU Jie (周洁); CHEN Hong (陈宏); MA Tao (马涛); MA XueLing (马雪玲); WANG HuaXin (王华新); SHU BaoZhen (舒宝珍); TANG Ling (唐玲) (中西医结合护理)
Traditional Chinese Medicine (TCM) exercise therapy is an important branch of TCM nursing. This paper summarized and combed the history origin of the TCM exercise therapy, and briefly discussed its development and application of theory in seven main historical stages. The TCM exercise therapy mainly focuses on treatment, and gradually incorporates the purpose of prevention, fitness and rehabilitation, which guides human exercise practice. (中医运动疗法是中医护理的重要分支。本文总结并梳理了中医运动疗法发展的历史源流, 简述其发展及应用经历的七个主要历史阶段。中医运动疗法以治疗为主, 逐渐纳入预防、健身、康复的目的, 指导着人类的运动实践。)